PERENCANAAN PONDASI GERBANG TOL KUTANEGARA PROYEK TOL JAKARTA-CIKAMPEK II BERDASARKAN DATA CONE PENETRATION TEST (CPT) - Fitri, Siti Nurlita; Pradana, Erik Wahyu (Jurnal Riset Rekayasa Sipil, 2023)
The Jakarta Cikampek II Toll Road has several toll gates that require an analysis of the substructure against the load from the upper structure, one of them is the Kutanegara Toll Gate. The design of the substructure (foundation) is calculated based on upper loads and reactions from the superstructure. This study aims to analyze the bearing capacity of the deep foundation due to the reaction of the upper structure. As a result, this analysis ensures the safe condition of the infrastructure system. The method of this study use bearing capacity analysis based on the Cone Penetration Test (CPT) investigation with the Schmertmann and Nottingham Approach which is combined with the calculation of pile group efficiency using the Converse-Labarre formula. Based on the results of a soil investigation using CPT, the subgrade is clay soil at a depth of 0-10m with a qc value of 30-160 kN/m2 with a γ value of 18-20 kN/m3 and a cohesion of 50 kN/m2. The bearing capacity result at a depth of 10m reaches 428.71 kN. The pile configuration uses 2x2 piles with a diameter of 40cm and a pile cap size of 2m x 2m. The maximum Pu describes 193.6 kN, this value is still less than the bearing capacity of the pile which means the safety condition. This research is expected to be a reference for the analysis of the bearing capacity of the bottom structure for related toll gate designs.